The role of fracture in dynamic tensile responses of fractured rock mass: Insight from a particle-based model - Changtai Zhou; Yichao Rui; Jiadong Qiu; Zhihe Wang; Tao Zhou; Xiting Long; Ke Shan (International Journal of Coal Science & Technology)
Abstract The fractured rock mass inherently exhibits uncertainty due to the presence of pre-existing discontinuities. In this study, a particle-based model incorporating the discrete fracture network (DFN) to elucidate the dynamic tensile responses and associated uncertainty of rock mass. At first, the particle-based model was used synthesize the intact rock and split Hopkinson pressure bar (SHPB) system, while the fractures were represented using the smooth fracture model (SJM). Subsequently, the samples of the fractured rock mass with varying joint geometrical configurations were conducted the dynamic tensile test using the numerical SHPB system. The simulated results demonstrate a gradual decrease in dynamic tensile strength (TS) with increasing fracture intensity and fracture length, which can be effectively described by nonlinear exponential functions. Additionally, the fracture orientation significantly influences the dynamic TS, however, the anisotropic characteristics gradually diminish as the deviation angle approaches 90°. Furthermore, as fracture intensity and fracture length increase, the dynamic TS variability also rises steadily. However, no noticeable pattern is seen when considering cases with varying fracture orientations. When subjected to SHPB loading, the fractured rock mass primarily exhibits a combined tensile-shear failure mode, contrasting with the pure tensile failure mode exhibited by the intact rock. These findings contribute significantly to comprehending the dynamic tensile responses of the fractured rock mass and can further enhance the stability analysis of in-situ rock engineering.